Isolation And Identification Of Protease Producing Bacteria From Various Sources Related To Hevea Brasiliensis - Pauzi, Norlin (2011)
Screening and isolation of proteolytic bacteria were carried out from Hevea brasiliensis tree including from bark, fresh latex, coagulated rubber, soil around the tree, latex from processing tank, residual latex on soil and effluent from effluent treatment pond. Fifteen isolates showed hydrolysis on 10 % of skim milk agar, indicating protease production from these isolates. Among the isolates, three were identified as Bacillus sp. and were selected for further study, designated as Strain K, Strain M and Strain O. Strain K and Strain O showed growth temperatures as high as 45 ºC within a broad pH range of 4 to 10.